6(x-7)+4=6x+7

Simple and best practice solution for 6(x-7)+4=6x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-7)+4=6x+7 equation:


6(x-7)+4=6x+7

We simplify the equation to the form, which is simple to understand
6(x-7)+4=6x+7

Reorder the terms in parentheses
+(+6x-42)+4=6x+7

Remove unnecessary parentheses
+6x-42+4=+6x+7

We move all terms containing x to the left and all other terms to the right.
+6x-6x=+7+42-4

We simplify left and right side of the equation.
0x=+45

0=45

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| -3b+3b= | | -9+5x=31 | | 3(X+5)+4(2X-8)=5(2X+1) | | 6x+4+4x+9=9x+3 | | 0.8x-12=1.3x-17 | | 0.17x+0.7(x-2)=0.01(4x-1) | | x+5/2=15-x/3 | | 4p+3=5+3p | | X(3X-14)=-9 | | -2(4y-3)-y=-2[y-3) | | 6.2x-3=5.2 | | x+1.6x=88 | | 12+9*n=6 | | 6b+8=3b-12 | | 3.8+4=2.8x | | 12+9xn=6 | | 3.8+4=28x | | x+1.6x=87 | | 3-12= | | s=qs+q | | 6(h+3)-7h-4= | | b=qs+q | | x+1.6x=96 | | 2(3x-4)=4x+12 | | x^2+jx+6=0 | | 1/3(6y-9)=-2y+13 | | x-1=6x-18 | | 5x-7/3-4=3/5-2+5x/6 | | 2x-x+9+3x-3=16 | | 3(y+1)-y=2y+3 | | 5x-11x-12=0 | | 3.2+0.4= |

Equations solver categories